Preparation of La-Cr Perovskite Coating Using Electrodeposition Method. Issue 14 (1st January 2016) - Zhang, Xue; You, Pengfei; Luo, Mengqi; Zeng, Chaoliu
Abstract : An adhesive LaCrO3 perovskite coating has been prepared on stainless steel substrate by cathodic electrodeposition from aqueous solution 0.03 M La(CH3 COO)3 + 0.03 M CrCl3 + 0.03 M Na3 C6 H5 O7, followed by heat-treatment at 800°C in air. The electrodeposition of La-Cr coatings has been examined in the solution with pH of 2∼3 at the current density of 1∼5 mA cm −2 . It is shown that the change of pH by even 0.1 can affect obviously the deposition of La-Cr coatings, and increasing the current density will lead to the generation of more cracks in the coatings. A more uniform and compact La-Cr coating can be obtained in the solution with the optimized pH value of 2.7 at the optimized current density of 1 mA cm −2 . The La and Cr deposits change from their metallic states to the hydroxides during electrodeposition, corresponding to the increase in the pH with time. The as-prepared La-Cr coating is rich in La, due to the strong coordination of trivalent chromium with complex agent in the bath. The outward diffusion of Cr from the stainless steel substrate supplies the as-prepared La-rich coating to form LaCrO3 during heat-treatment.